Risk of second primary cancers in patients with rectal neuroendocrine neoplasms: a surveillance, epidemiology, and end results analysis - Wan, Ming; Wu, Jiaqi; Jiang, Zhaopeng; Gong, Wushuang; Zhou, Xianli (Frontiers in Oncology, 2023)
Background: While an elevated risk of second primary cancers (SPCs) has been observed in many other cancers, risk of SPCs has not been quantified in patients with rectal neuroendocrine neoplasms (NENs).Methods: Survivors of primary rectal NENs diagnosed between 2000 and 2018 were identified from the Surveillance, Epidemiology, and End Results (SEER)-18 registries. Relative risk of SPCs was estimated as the standardized incidence ratio (SIR), which was calculated using SEER*Stat software.Results: Between 2000 and 2018, a total of 15836 patients diagnosed with rectal NENs, of whom 1436 (9.1%) received diagnosis of SPCs (SIR:1.19, 95%CI: 1.13-1.26). The majority of patients were aged 50-69 and had their first cancer diagnosed at the localized stage. Male survivors had a higher propensity for developing SPCs overall, while female survivors exhibited higher risks of specific SPCs. Age at diagnosis of rectal NENs influenced the risk of SPCs, with younger patients having greater risks. A statistically significant increase in the incidence of SPCs was observed among patients aged 30-64 years. Black patients had higher relative risks of certain SPCs, while White patients had a lower risk of subsequent melanoma. Trend analysis revealed that the highest excess burden of SPCs was observed in the years 2000 to 2002. Risk of SPCs remained elevated within the first four years post-diagnosis for survivors of rectal NENs, but diminished thereafter.The study revealed that individuals who survived rectal NENs were at an elevated risk of developing SPCs compared to the general population. Our results hold important implications for the formulation of lifelong surveillance recommendations for cancer survivors.